Proposição de melhores práticas de gestão para o preenchimento dos relatórios sucupiras dos programas de pós-graduação - Teixeira, Girlei Dario Zemolin (2019)
The research activities in Brazil are concentrated in the courses and graduate programs of the universities, but in these institutions there is no single function of researcher, and the teachers of the Graduate program perform the functions of faculty and Researcher, as well as other activities, such as: taking administrative, extension and representation functions. This study aimed to analyze the completion of the reports of the Sucupira platform system, an online tool used to collect information, perform analyses, assessments and serve as a reference base for evaluating the programs of Postgraduate studies in Brazil. The post-graduation programs of the Federal University of Santa Maria-UFSM were considered of excellence, that is, they obtained concepts from 5 to 7 in the last four-year evaluation of CAPES (2013 – 2016). In this sense, through research with PPG ´ s, this study sought to propose practices that can help PPG ´ s coordinators to improve the completion of reports in the Sucupira platform, which can also influence the final concept given to the course by Capes. Thus, the final result of this study was to present a report model, proposing to PPG ´ s what can be considered the best practices for completing the items evaluated by CAPES in the Sucupira platform.